Proceso logístico en la Empresa Plastivill S. A. de la ciudad de Babahoyo, periodo 2022. - Gonzales Cando, Jeniffer América (2023)
The present case study called "Logistic process in the company Plastivill S. A of the city of Babahoyo, period 2022", related to the research line "Financial Management, Administrative, Tax, Audit, Control" and the sub-line "Companies and Public and Private Institutions" aims to analyze the logistics processes carried out in the company Plastivill, the importance of conducting this case study lies in the opportunity that the company has through a thorough analysis of its logistics process to make decisions to improve the current system that is leading the entity. For the development of this work, it was necessary to identify the shortcomings in the supply, storage, distribution and dispatch processes. To evidence the conditions that gave rise to these problems, descriptive and analytical methods were used, which allowed obtaining information through an interview with the manager and a survey of employees involved in the logistics phases, which showed that this process developed by the company has shortcomings in its implementation, in conclusion, the problem is linked to the lack of implementation of a logistics area in the company, likewise emphasizes the hiring of trained personnel to carry out these processes and the constant training of personnel to mitigate errors and create a competitive advantage in the market.